Effects of HIITon the mood of overweight people in virtual and face-to-face training - Rojas Ilama, Víctor Daniel (2022)
The main objective was to compare the effects of 35-minute HIIT session, in both virtual and face-to- face modes, on the mood and the perceived effort of overweight people. A total 13 people (5 men and 8 women) were recruited, in an average age of 37.85 ± 13.20 years (17-60 year range), who were randomly assigned to each of the three conditions (control, face-to-face training, virtual training). Prior to and immediately after each of the interventions, the POMS test was applied in order to measure mood. The measuring of perceived effort (PE) was carried out at the end of each of the HIIT exercises (it was not assessed during warm-up or return to calm). When a 2-way repeated-measure ANOVA was applied (condition [3] x measurement [2]), it was found that both stress and vigor after applying face-to-face treatment showed a significant increase. In addition, stress increased in the virtual session. For their part, the PE values reported in the measurements of the face-to-face and virtual sessions were above those suggested in the literature. In conclusion, a HIIT session for overweight people, whether face-to-face or virtual, shows similar results in their moods, except for vigor, which only increases in the face-to-face situation. The other variables showed a similar behavior.